2016
DOI: 10.1007/s11896-016-9207-8
|View full text |Cite
|
Sign up to set email alerts
|

Police Strategies and Suspect Responses in Real-Life Serious Crime Interviews

Abstract: This research focuses exclusively on real-life taped interviews with serious crime suspects and examines the strategies used and types of questions asked by police, and suspects' responses to these. The information source was audio-tape recorded interviews with 56 suspects. These recordings were obtained from eleven Police Services across England and Wales and were analysed using a specially designed coding frame. It was found that interviewers employed a range of strategies with presentation of evidence and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Legal psychological examinations of interviews have generally focused on interviewer behavior, and characterized suspect responses insofar as they reflect a response to the interviewers questioning style (e.g. Leahy-Harland & Bull, 2017). This work has been incredibly valuable in improving the practice of investigative interviews and understanding how interviewer behavior impacts upon the cooperation of the suspect.…”
Section: Suspect Behaviors During Investigative Interviewsmentioning
confidence: 99%
“…Legal psychological examinations of interviews have generally focused on interviewer behavior, and characterized suspect responses insofar as they reflect a response to the interviewers questioning style (e.g. Leahy-Harland & Bull, 2017). This work has been incredibly valuable in improving the practice of investigative interviews and understanding how interviewer behavior impacts upon the cooperation of the suspect.…”
Section: Suspect Behaviors During Investigative Interviewsmentioning
confidence: 99%
“…Humanitarian interviewing was also predictive of suspects' self-reported cooperation during the interview. By contrast, Goodman-Delahunty et al (2014) also assessed cooperation (though not confession) and reported that confronting suspects with evidence actually promoted resistance rather than cooperation (but see Bull, 2014, andLeahy-Harland &Bull, 2017, who found gradual disclosure of evidence/information to be associated with keeping suspects of serious crimes 'on topic'). Goodman-Delahunty et al…”
Section: Introductionmentioning
confidence: 99%
“…ethics, but also its effectiveness(Walsh, Oxburgh, Redlich & Myklebust, 2016). For suspect interviewing in connection with high risk crimes, such as murder, sexual offences, and terrorism, research has shown that humane styles of interviewing are positively associated with the gaining of information partly by enabling an environment where suspects feel comfortable and willing to cooperate(Alison, Alison, Noone, Elntib, & Christiansen, 2013;Holmberg & Christianson, 2002; Kebbell, Hurren, & Mazerolle, 2006;Leahy-Harland & Bull, 2016).…”
mentioning
confidence: 99%